A comparison of the university rankings and educational backgrounds for university supervisors in teacher education - Manning, Dionna Draper (East Carolina University, 2015)
As the demand for highly qualified teachers continues to increase, additional pressure is placed on teacher accountability and teacher education preparation programs to demonstrate their value and become more cost effective. Teacher education preparation programs incorporate a range of field experiences throughout the course of study; including observations, direct instruction practica, and culminating, supervised P-12 internships. Designed to give education candidates real world experiences in actual class settings with field experts, authentic internship experiences help mold pre-service teachers into prepared educators (Turunen & Tuovila, 2012). Strategically placed at the end of the preparation program to tie together content knowledge and pedagogy, the internship experience has been identified as one part of teacher preparation that has had the largest influence on the development of new teachers. The internship experience is comprised of a team of different members including the intern, the clinical teacher, and the university supervisor. Each member of the team must converge to provide guidance and support for a meaningful experience for the student intern. Loughran’s research validates the need for university supervisors to provide direct support and constructive feedback when working with interns, out of a concern that without specifics and effective support the reflection will be viewed as a lesson overview or summary by the intern (Sewall, 2009). University supervisors set the stage and continue with feedback so interns can effectively evaluate themselves and grow as educators. The purpose of this study was to analyze the feedback provided by university supervisors in an elementary education internship to determine if the university rankings and educational backgrounds impacted the feedback provided. This quantitative study evaluated the feedback provided by each university supervisor and compared it with the supervisor’s education level, degree area, institutional ranking, and tenure status. Analysis of the data revealed that there were no significant differences in the feedback provided by university supervisors in post observation progress reports. The university rankings and educational backgrounds of the university supervisors did not significantly affect the feedback provided to the interns during the internship experience. Additional studies are needed to validate these results and extend them into longitudinal studies.
Comparison of the university rankings and educational backgrounds of university supervisors in teacher education
Keywords: University supervisors; Teacher education; Interns (Education)--United States; College teachers--United States; Student teaching--United States; Teachers--Training of--United States